Dynamic mechanical properties and swelling behavior of Filled Liquid Silicon Rubber - Özkan, Betül Çiçek; Kaschta, Joachim (My University, 2015)
Materials having the properties which are changed with the effect of magnetic fields belong to the group of smart materials and these are known as magnetorheological materials. Liquid Silicon Rubber (LSR) having the applications as liquid or elastomer is present in this group. Magnetorheological property is obtained by filling of liquid Silicon with iron particles. In this study, the influence of concentrations of spherical carbonyl iron particles on both viscoelastic properties and cross-linking behavior of liquid silicon was figured out. Polymer networks were synthesized by reacting of a commercially available chemical namely divinyl Polydimethylsiloxan [(CH3)2SiO]n containing platinum catalyst with a cross-linker namely methyl hydrogen siloxan (CH3(H)Si-O). In the structures of both chemicals, there are nano-silica (SiO2) particles. Rheological characterization of liquid silicon was carried out in a rotational Rheometer by dynamic mechanic test. Enhancement in the cross linking density and acceleration in the polymer network formation rate were observed with increasing temperature. SiO2-Particles/PDMS-Matrix and particle/particle interactions were found to occur with the increasing amount of filler material. In addition, it was observed that relaxation time and hence the frequent dependence of elasticity modulus (G’) was changed. Cross-linking behavior of the elastomer was examined by swelling test, and it was figured out that crosslinking density (interaction at the particle/matrix interface) was increased with the increasing amount of filler material.
Diğer - Poster
Keywords: Swelling; Cross linking; Liquid silicon rubber